Intercultural Communicative Competence In English Textbook Entitled Bahasa Inggris Tingkat Lanjut: A Content Analysis - Alif Prasetya; Teguh Sarosa (CV Putra Publisher, 2026)
This study examines the representation of Intercultural Communicative Competence (ICC) in the reading texts of the Indonesian EFL textbook Bahasa Inggris Tingkat Lanjut and analyzes the distribution of cultural types. Despite increasing research on ICC in EFL materials, limited studies have specifically investigated how ICC components are systematically represented in textbooks used under the Merdeka Curriculum. Using a descriptive quantitative content analysis, 13 reading texts were analyzed based on Byram’s framework (1997; 2021), which includes five components: savoirs, savoir être, savoir comprendre, savoir apprendre/faire, and savoir s’engager. Cultural content was categorized into source, target, and international cultures. The findings reveal that all ICC components are present but unevenly distributed. Savoirs is the most dominant, while savoir comprendre is the least represented, indicating a stronger emphasis on cultural knowledge and values than on interpretive and interactive skills. International culture is the most prominent, followed by a balanced presence of source and target cultures, although their depth varies. Overall, ICC integration remains partial and unbalanced. The study highlights the need for more comprehensive integration of intercultural dimensions to support students’ holistic competence in line with the Merdeka Curriculum.